Efektivitas konseling behavioral dengan teknik self-management untuk meningkatkan disiplin belajar siswa - Dio Rizky Adirama; Putu Ari Dharmayanti; Dewi Arum Widhayanti Metra Putri (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
The research was conducted with the intention of seeing the effectiveness of behavioural counselling theory with self-management techniques in the improvement of student study discipline. In the design of this study, a quasi-experimental design with a non-equivalent post-test control group design was used. Participants were 10th grade students from SMK Negeri 2 Singaraja. The sampling was carried out by means of random sampling of the class as an attack group. As for the members of the sample are students of class X kuliner 5 and X kuliner 6, total 69 people as experimental and control class. The method used to analyse the data is the t-hit test using the program SPSS v.25 for Windows. The data collection instrument used is the study discipline questionnaire. This study uses behavior theory with self-management techniques to improve learning discipline among students in grade X in SMK Negeri 2 Singaraja. Based on the results of this study, t=2.705 and ES=0.64, p<0.05, we can accept Ha and reject Ho.